Pengaruh Kualitas Produk Dan Desain Terhadap Keputusan Pembelian Sepeda Motor Yamaha Cabang Pettarani Kota Makassar - andi rifka darang (Journal of Business Issues, 2022)
This study aims to determine the effect of quality of product and design on purchasing decisions of Yamaha’s motorbikes at Pettarani Makassar Branch. This study uses a quantitative method by distributing questionnaires. The sampling technique used non probability sampling, puprosive sampling technique and used 100 respondents for the sample. The analytical method used is multiple linear regression analysis. The results of this tudy state the quality of product and design both has a positive and significant effect on the decision to purchase a Yamaha’s motorbikes at Pettarani Makassar Branch. The results of the coefficient of detemine (R2) Obtained a value of 0,600. This shows that the purchasing decision variable is influenced by the quality of product and design variables which are highly influential.